The Ability of Early Childhood Education Teachers in Counseling Communication in East Kalimantan - Robingatin Robingatin; Lina Revilla Malik; Anis Komariah (Southeast Asian Journal of Islamic Education, 2022)
The background of this research is that Early Childhood Education teachers play an important role in interactions both as teachers in learning and as mentors and counselors for children. PAUD (Early Childhood Education) teachers are expected to have counseling communication skills, including empathy, active listening, and the ability to ask questions. This research aimed to find out the ability of Early Childhood Education Teachers in East Kalimantan in counseling communication. The research design was descriptive qualitative. The subjects in this study were Early Childhood Education Teachers from 8 PAUD institutions in 4 (four) City Districts in the East Kalimantan regions. There are Samarinda, Bontang, Kutai Kartanegara, and Kutai Timur. This subject was taken purposively from two teachers selected in each institution that was used as a place of research. The research object was the teacher's ability to conduct counseling communication by attending, empathizing, asking questions, and active listening skills. From this study, the researcher concluded that most Early Childhood Education Teachers can empathize but have not implemented empathic communication and effective listening in asking questions to explore children's emotions and thoughts. Most teachers used advising, seducing, persuading, and diverting children's problems in counseling communication. For further suggestions, school principals should evaluate the teachers’ ability in counseling communication to children and implement teacher counseling communication through tutorials and training among colleagues or peer tutors among teachers.